Laparoscopic appendectomy as the gold standard: What role remains for open surgery, conversion, and disease severity? - Claus Schildberg; Ulrike Weber; Volker König; Marius Linnartz; Sophie Heisler; Jennifer Hafkesbrink; Marcia Fricke; René Mantke (World Journal of Emergency Surgery)
Abstract Background Acute appendicitis is a common abdominal surgical emergency and is a major cause of acute abdomen in more than 20% of cases. Although various studies have been conducted in recent years on topics such as surgical techniques and antibiotic treatment of appendicitis, today there is a lack of large-scale studies focused on the different severity levels of acute appendicitis and their management. The study aimed to analyze the severity, types of surgical techniques, and mortality associated with acute appendicitis to identify possible developments. Methods We conducted a retrospective multicenter observational study based on routine data from 2010 to 2022. Patients over 18 years old with acute appendicitis were included and the following data were collected: patient demographics, comorbidities, type of surgery, complications, admission to ICU, length of stay, and in-hospital mortality. A total of 31,988 patients were included in the study. Results At the end of the study, 97.0% (P < .001) of the patients underwent laparoscopic appendectomy, with 86% of cases involving closure of the appendix stump by stapler (P < .001). It was only from 2014 onwards that more than 90% of surgeries were performed laparoscopically, and from 2017, this figure rose to 95%. Complicated appendicitis was present in 27.4% of cases. The distribution of severity was as follows: unspecified acute appendicitis in 39.5%, appendicitis with local peritonitis in 33.1%, appendicitis with local peritonitis and perforation in 17.1%, appendicitis with peritoneal abscess in 5.4%, and appendicitis with generalized peritonitis in 4.9%. Women had a significantly lower risk for conversion to an open operation than men (P < .001). The highest morbidity was observed in the group that converted from laparoscopy to open surgery (P <.001). Non-surgical treatment of appendicitis was not relevant, accounting for only 4% of cases. Conclusion Since 2017, primary laparoscopic appendectomy has been the gold standard for even complicated acute appendicitis (> 95% annually). Over three-quarters of patients undergo an appendectomy with a stapler, making this surgical technique the preferred method of laparoscopic surgery in Germany. Patients who undergo an interoperative switch to open therapy should be considered a subgroup at risk of increased mortality. Trial registration ClinicalTrials.gov ID: NCT06558760.